The Effect Of Tax Amnesty Policy, Exemption Of Transfer Fees, Tax Socialization, And Service Quality On Motor Vehicle Taxpayer Compliance In Madiun Regency - Taufiq Shiqdi Huda; Wijianto; Sri Hartono (PT. Anagata Sembagi Education, 2024)
The government always strives to carry out national development in all fields. The goal of national development is to create a just and prosperous society. In this effort the community is expected to be able to participate voluntarily through taxes, because to support these efforts the Government requires large costs. Every year the Government tries to maximize tax revenues to finance state expenditures because, the higher the tax revenue, the higher the state's ability to finance national development. Efforts to increase potential sources of income are by encouraging public enthusiasm in fulfilling their obligations as taxpayers so that they can foster awareness and compliance in paying taxes. One of them is the East Java Provincial Government launching a Policy or Program to increase regional income while growing awareness and compliance in paying taxes. Given the arrears in East Java 1.9 million taxpayers while in Madiun District 35,388 taxpayers who are in arrears. The purpose of this study was to examine the effect of tax whitening policies, exemption from transfer fees, tax socialization and service quality on motor vehicle taxpayer compliance in Madiun Regency, either partially or simultaneously. This study uses respondents, namely taxpayers who are registered in the SAMSAT of Madiun Regency for the period 2020. The sampling technique in this study is incidental sampling using the formula for calculating the amount of Slovin. The results showed that simultaneously (simultaneously) the policy of tax whitening, exemption from transfer fees, tax socialization and service quality had an effect on the compliance of motorized vehicle taxpayers. While partially the tax whitening policy has a significant positive effect on motor vehicle taxpayer compliance, the exemption of transfer fees has a significant negative effect on motor vehicle taxpayer compliance, tax socialization has a significant positive effect on motor vehicle taxpayer compliance and service quality has a significant positive effect on mandatory compliance. vehicle tax.